30â75-day Sea Level Variations in The Equatorial Indian Ocean as Observed by Satellite Altimeter - Iskhaq Iskandar (Institut Teknologi Bandung, 2011)
Basin-wide structure of intraseasonal sea level variations in the equatorial Indian Ocean is investigated using satellite altimeter data. The spectral analysis reveals that the intraseasonal sea level variations are dominated by the 30-75-day oscillations. The spatial amplitude structures of the intraseasonal sea level inferred from the complex empirical orthogonal function (CEOF) analysis show a typical structure of equatorial Kelvin and off-equatorial Rossby waves. Moreover, the spatial phase structures of the CEOF mode reveal eastward propagating signal. The estimated phase speed does not correspond exactly to that of one particular baroclinic modes though it falls within the range expected for the first three baroclinic modes in the Indian Ocean. This may suggest that the propagating signals do not involve a single baroclinic mode, but instead the first, second and possibly higher baroclinic modes.